Therapy of spinal cord injury by folic acid polyethylene glycol amine-modified zeolitic imidazole framework-8 nanoparticles targeted activated M/Ms - Li, Qi; Guo, Yue; Xu, Chang; Sun, Jiachen; Zeng, Fanzhuo; Lin, Sen; Yuan, Yajiang (Frontiers in Bioengineering and Biotechnology, 2022)
Excessively activated microglia/macrophages (M/Ms) re-establish the proinflammatory microenvironment that exacerbates motor and/or sensory dysfunction after spinal cord injury (SCI). Thus, proinflammatory M/Ms-suppressed treatments may be effective strategies for SCI. However, the utilization of anti-inflammatory drugs for clinical approaches and biomedical research has side effects, such as nephrotoxicity and hepatotoxicity. In this study, we fabricated folic acid-polyethylene glycol (FA-PEG) amine-modified zeolitic imidazole framework-8 (ZIF-8) nanoparticles (FA-PEG/ZIF-8) and found that it effectively restored function in vivo. FA-PEG/ZIF-8 treatment significantly eliminated proinflammatory M/Ms without targeting other nerve cells and downregulated inflammation in the injured lesion. Furthermore, FA-PEG/ZIF-8 caused little toxicity in SCI mice compared to normal mice. These results suggest that FA-PEG/ZIF-8 has the potential to help recover from early-stage SCI by suppressing proinflammatory M/Ms.